2010
DOI: 10.1002/pssc.200982761
|View full text |Cite
|
Sign up to set email alerts
|

A new structure of counter electrode used for dye‐sensitized solar cells

Abstract: An ATP‐fueled soft gel machine reconstructed from polymer‐crosslinked actin muscle protein (“giant‐actin”) and analogously modified myosin has been built by Osada and co‐workers. The “giant‐actin” gel filaments (several 1000 times larger by volume than native actin, see Figure) move along their myosin counterparts as fast as native F‐actin. Such machines should work inside their body of origin without eliciting immunoreactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This is because we have to consider other properties like the conductivity of the catalyst film and the reflectivity; so the surface advantage of the platinum nanoparticle CE is reduced. We found that by placing a reflecting silver thin layer on the non conductive back side of the CE we obtain an improvement in the I-V parameters, reaching a solar cell efficiency of 4.75% with a corresponding J sc of 12.87 mA cm À2 , a fill factor of 0.56 and a V oc of 0.66 V. Obviously, the use of a back reflector imply to renounce to the transparency of the DSSC, which is important from aesthetic point of view, but the advantage is a gain in efficiency as reported in literature from Ji et al 22 We used this special counter-electrode to show that the second key factor is not the conductivity of the CE, which is limited by the conductivity of the photoanode and by the internal resistance of the cell, but is the light reflected from the back side. In fact, the special silver CE had a roughness of 5.5 nm, which, combined with the mirror effect, overcomes the Pt mirror sputtered CE efficiency.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…This is because we have to consider other properties like the conductivity of the catalyst film and the reflectivity; so the surface advantage of the platinum nanoparticle CE is reduced. We found that by placing a reflecting silver thin layer on the non conductive back side of the CE we obtain an improvement in the I-V parameters, reaching a solar cell efficiency of 4.75% with a corresponding J sc of 12.87 mA cm À2 , a fill factor of 0.56 and a V oc of 0.66 V. Obviously, the use of a back reflector imply to renounce to the transparency of the DSSC, which is important from aesthetic point of view, but the advantage is a gain in efficiency as reported in literature from Ji et al 22 We used this special counter-electrode to show that the second key factor is not the conductivity of the CE, which is limited by the conductivity of the photoanode and by the internal resistance of the cell, but is the light reflected from the back side. In fact, the special silver CE had a roughness of 5.5 nm, which, combined with the mirror effect, overcomes the Pt mirror sputtered CE efficiency.…”
Section: Resultsmentioning
confidence: 70%
“…Obviously, the use of a back reflector imply to renounce to the transparency of the DSSC, which is important from aesthetic point of view, but the advantage is a gain in efficiency as reported in literature from Ji et al 22 We used this special counter-electrode to show that the second key factor is not the conductivity of the CE, which is limited by the conductivity of the photoanode and by the internal resistance of the cell, but is the light reflected from the back side. In fact, the special silver CE had a roughness of 5.5 nm, which, combined with the mirror effect, overcomes the Pt mirror sputtered CE efficiency.…”
Section: Resultsmentioning
confidence: 98%